Orchestration of Renewable Generation in Low Energy Buildings and Districts Using Energy Storage and Load Shaping. (November 2015) - Tuohy, P.; Kim, J-M.; Samuel, A.; Peacock, A.; Owens, E.; Dissanayake, M.; Corne, D.; Chaney, J.; Bryden, L.; Galloway, S.; Stephen, B.; Santonja, S.; et al.
Abstract: There is increasing penetration of renewable generation in buildings and districts. There are challenges in making the effective use of this generation. The objective of the ORIGIN project (Orchestration of Renewable Integrated Generation In Neighborhoods) is to shape loads so that the fraction of energy consumed that is from local renewable generation is maximized, and energy imported from outside sources is minimized. This paper presents the overall approach taken in the ORIGIN project and explores building physics aspects of solar thermal storage system orchestration. The case study districts are briefly introduced and characteristics of their generation, buildings, districts and shiftable loads described. The orchestration approach taken in ORIGIN is then presented. At the core of the ORIGIN system is the orchestration algorithm which generates informational and control outputs to shape future loads to best meet the objectives. The model based approach used to quantify thermal and electrical load shifting opportunities for pre-charging, coasting or avoiding loads, while meeting thermal comfort and other demands, is described using a solar thermal storage system as an example. The future steps for the ORIGIN project; retrofit of the ORIGIN system into existing districts and potential for other future applications is briefly discussed.